Characteristics of RN to BSN students in online programs. (June 2020) - Hensley, Angie; Wilson, Jessica L.; Culp-Roche, Amanda; Hampton, Debra; Hardin-Fanning, Frances; Cheshire, Michelle; Wiggins, Amanda T.
Abstract: Background: Registered nurse to baccalaureate in nursing (RN-BSN) programs has rapidly moved to online formats to increase the ability of working nurses to earn their BSN degree. Nursing faculty are tasked with designing programs to meet the needs of the nursing workforce using best practices for online learning. Objectives: Describe RN-BSN student perceptions of their online programs, including clinical experiences. Specific aims were: 1) evaluate student satisfaction in online courses, 2) describe experiences students were required to have to meet clinical objectives, 3) determine generational differences in satisfaction with online learning 4) determine the students' perception of the value of course content in online program 5) examine life responsibilities impacting student program participation. Design: A descriptive cross-sectional design with convenience sampling was used. Setting: Participants included 43 RN-BSN students currently enrolled in at least one online course at one of six accredited nursing programs across the United States. Methods: Survey data were collected over 4 months in the summer of 2019. The research team created a 9-item online survey, including investigator-initiated questions and demographic information. Results: Overall satisfaction in online programs was high. Technology, nursing informatics, computer classes, research and evidence-based practice, public health, pathophysiology, pharmacology, leadership, reading text books, assessment, brushing up on skills, and emotional intelligence were most valued content. Least valued content included discussion boards and group projects. Clinical requirements and setting varied across programs. Life responsibilities impacted students' participation in online programs. Conclusions: Overall, students were satisfied and found value in their online RN-BSN coursework. Clinical experiences varied between RN-BSN programs and participation in online courses was impacted by extracurricular obligations. Based on this study, more data regarding what could be counted as clinical hours is needed. Faculty need to consider alternative ways to achieve learning outcomes. This study's outcomes may help guide faculty in developing RN-BSN programs and student-centered courses.